Exploring the role of ions and amino acids in directing the growth of minerals from solutions - Piana, Stefano; Franca; Taylor, Zoe; Raiteri, Paolo; Gale, Julian (The Mineralogical Society, 2008)
The influence of both sulphate ions and aspartic acid on directing the growth of baryte has been explored using computer simulation. Both species are found to significantly reduce the activation freeenergy to growth under appropriate conditions, with the influence of sulphate being surface specific.This offers the potential for a new approach to morphology control without inhibition that may have implications for biomineralization.